Study of selected livestock innovations in Ethiopia - Azage Tegegne; Getachew Legese Feye (University of Bonn, Center for Development Research (ZEF), 2020)
Ethiopia is endowed with significant livestock resources and holds the largest livestock population in Africa, estimated at around 60 million cattle, 60 million sheep and goats, 52 million chickens, 4.5 million camels, 10 million bee colonies and 7.2 million equines. The livestock production and management system in Ethiopia is mainly extensive, where indigenous breeds are kept under lowinput/low-output husbandry practices. This study is part of a multi-country African livestock innovation study covering three East and West African countries (Ethiopia, Kenya and Mali) supported by the Program of Accompanying Research for Agricultural Innovation (PARI). The purpose of the study was to provide guidance to policy makers and private and public investors on promising innovations in Ethiopian livestock value chains and their contexts, which could enable transformation of the livestock sector. The study also aimed at providing private and public decision-makers with guidance on investment opportunities building on a review of broad trends of Ethiopian livestock development and in-depth analyses of success stories from selected innovations to encourage wider lesson-learning and knowledge-sharing. The study is based on a desk review of important documents, key informant interviews, consultations with major stakeholders on respective innovations and analyses of official customs data and other data from the national statistical agency of the country. The study focused on four selected livestock innovations: beekeeping, feed production and marketing, integrated feedlot operation and index-based livestock insurance. These innovations were selected at an inception workshop held in Kenya, Nairobi, in October 2019. Results of the study reveal the possibility to increase honey production six fold through improved frame hive, from the current level of 15-20 kg/hive/year to 90-120 kg/hive/year by raising farmers' skill and knowledge on apiary site management, and facilitating access to inputs. On the other hand, an assessment of feed innovations revealed attractive investment opportunities in the harvesting, conserving and proper utilization of crop residues, hay and other feed resources. Harvesting and conservation of crop residues alone can create employment opportunities for over 245,000 youths for two months a year. Investments in industries that produce feed premixes and additives to supply the Ethiopian livestock sector also hold promise, in light of imports over 4,000 tons of these feed ingredients per annum an. Investment in integrated feed production, feedlot operation, slaughter and export of beef is also indicated as an promising business opportunity to enhance benefits from the Ethiopian beef industry. Index-based livestock insurance is also found to be a scalable innovation in the Ethiopian livestock industry that can benefit both livestock producers and the financial sector actors. The study has shown adoption and impact, trade-offs/externalities, potential for scaling and broad policy and development implications of all the four selected livestock innovations in Ethiopia.
Keywords: O13; O30; O33; Q16; 330; Livestock innovations; beekeeping; feeds; premixes; integrated beef production; IBLI